Alterações motoras, cognitivas e neuroquímicas causadas pela administração repetida da deltametrina em ratos - Souza, Marina Freire de (2015)
Studies have shown that pesticide exposure is a risk factor to Parkinson Disease (PD) development in urban areas and mainly in rural areas. One of these pesticides, Deltamethrin (DM), is used indiscriminately for vector control in crops, veterinary medicine and control of domestic pests. The aim of the study is investigate the motor, cognitive and neurochemical changes caused by repeated administration of DM in rats. 38 Male Wistar rats were used, 9-10 months-old, from the Neurophysiology Laboratory animal house of UFS. The study was divided into two experiments: (1) intranasal (i.n.) and (2) intracerebroventricular (i.c.v.). In the (1), the animals were divided into 2 groups (CTR, 0.9% saline solution, n=9) and DM 0.5 (treated with DM 0.5 mg, n=10), that received 3 infusions administrated one every 7 days. During the treatment, the animal were subjected to behavior test: catalepsy, novel object recognition task, spontaneous alternation and contextual conditioned fear. In i.c.v. experiment, the animals were divided into 3 groups: control (CTR, n=7); DM 0.5 (treated with DM 0.5 μg diluted in 2 μL, n=7) and DM 5 (treated with DM 5 μg diluted in 2 μL, n=5). In the experiment (2), the animals received 3 i.c.v. injections (2 μL/injection), one each 48 hours. During the treatment, the rats were submitted to behavior test: catalepsy, open field test and spontaneous alternation. After the behavior tests of both experiments, the rats were anesthized, perfused transcardially, their brains removed and submitted to Tyrosine Hydroxylase (TH) immunochemistry in Substancia Nigra pars compacta (SNpc), Ventral Tegmental Area (VTA) and dorsal striatum areas. In i.n. experiment, there were motor changes in open field and cognitive changes in novel object recognition task and contextual conditioned fear. The immunohistochemistry shows a reduction of TH+ cells in SNpc and VTA and an increase of Optical Density in dorsal striatum. In i.c.v. experiment, it was observed motor changes in open field and cognitive changes in spontaneous alternation. In immunohistochemical there was a decrease of TH + cells in DM 5ug animals in SNpc and VTA and decreased their levels in DM 0.5 g and DM 5 ug groups in the dorsal striatum. In both experiments, cognitive changes preceded the motor changes. The data presented contribute to understanding of physiological and behavioral changes after exposure to DM and more studies are needed to elucidate the DM as a possible cause of parkinsonism symptoms.